Is a Hybrid Teaching-Learning Model Feasible to Use in Language Classrooms? - Ginting, Daniel (Jurnal Bahasa Lingua Scientia, 2018)
This preliminary study aims at describing how a hybrid class has been implemented in English class of non-English Department students. The questionnaire of the online survey was employed to collect the primary data. About 25 students from Management Study Program became the subjects of the study. This study found most students had positive perceptions towards the implementation of the hybrid model in terms of the curriculum, assessment, classroom management, materials, teaching and learning activities, and teacherâs feedback. Despite the fact that most students favor the prevailing hybrid class, this combined model of the conventional and online learning is also subject to some weaknesses: time-consuming for giving feedback, copyright issues, the cost of buying the devices and internet connection service. Â